Pembinaan Pemanfaatan Pekarangan Untuk Meningkatkan Ketahanan Pangan di Desa Mampari Kecamatan Batu Mandi Kabupaten Balangan - Suparno; Tinting S, Ruben; Widyawati, Wahyu; Winerungan, Shella Agnessy Jullyta; Rumbang, Nyahu; Rahman, Arief (Lembaga Dongan Dosen, 2024)
In order to enhance the knowledge and abilities of rural farmers and to bolster food security, community service initiatives have been undertaken. This community service activity was conducted on the grounds that farmers in Mampari village, Batumandi subdistrict, frequently encounter challenges in meeting their vegetable consumption needs despite the availability of land in their yards that could be utilized directly. This has a negative impact that is not desired, such as a lack of vitamin and mineral intake and food fiber, a lack of benefits of vegetable consumption, and also due to the ignorance of farmers in efforts to utilize yard land by cultivating horticultural crops and processing plant products. The community service activity was conducted using three methods: lecture, written, and demonstration. The results of the service demonstrate a notable increase in knowledge and skills related to horticultural plant cultivation and management, processing techniques, and business opportunities. Specifically, there was an 85% improvement in understanding horticultural plant cultivation and management, a 90% increase in processing skills, a 75% rise in independence in processing and presenting horticultural products, and an 85% enhancement in understanding the potential economic value of horticultural plants. These outcomes highlight the effectiveness of the community service activities in enhancing the knowledge and skills of rural farmers, which in turn can contribute to improved food security.